2019
DOI: 10.3390/app9163398
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Solar-Assisted Air-Conditioning System Applied to a Remote School

Abstract: In this work, we present an absorption cooling system with 35 kW capacity driven by solar thermal energy, installed in the school of Puertecitos, Mexico, an off-grid community with a high level of social marginalization. The cooling system provides thermal comfort to the school’s classrooms through four 8.75-kW cooling coils, while a 110-m2 field of evacuated tube solar collectors delivers the thermal energy needed to activate the cooling machine. The characteristics of the equipment installed in the school we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The pump (SWP) suctions in the seawater stream (13) and conducts it as stream 14 to dissipate the heat of the exothermic reaction in the absorber and leaves at a higher temperature (stream 15=16) and is conducted to condense the steam (7) produced in the GEN. The stream (17), after receiving the condensation heat, leaves the condenser and enters the desalination subprocess and is taken to a stream divider (DIV), where it is divided into streams (18) and (21). The stream ( 21) is taken to a brine dilution vessel (BRC); while the stream (18) goes through an expansion process, so it flashes, due to the pressure decrease, and remains in two phases (stream 19).…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pump (SWP) suctions in the seawater stream (13) and conducts it as stream 14 to dissipate the heat of the exothermic reaction in the absorber and leaves at a higher temperature (stream 15=16) and is conducted to condense the steam (7) produced in the GEN. The stream (17), after receiving the condensation heat, leaves the condenser and enters the desalination subprocess and is taken to a stream divider (DIV), where it is divided into streams (18) and (21). The stream ( 21) is taken to a brine dilution vessel (BRC); while the stream (18) goes through an expansion process, so it flashes, due to the pressure decrease, and remains in two phases (stream 19).…”
Section: System Descriptionmentioning
confidence: 99%
“…This is mainly because there is a relationship between water scarcity and the availability of solar radiation in many regions [16]. On the other hand, absorption-cooling systems are efficiently coupled with solar heating technologies in regions with difficult access to electricity [17,18]. Currently, the trend is in the hybridization of technologies, seeking greater efficiency and less pollution [19], performing energy and mass integrations between the different streams.…”
Section: Introductionmentioning
confidence: 99%
“…In this period, several configurations have been studied and analyzed in terms of stages, absorberrefrigerant pairs, drive medium, applications and cooling capacities. In the literature, studies of solar cooling thermal systems have been found with single-effect absorption machines and driven by various types of solar collectors: with nonconcentrating or stationary solar collectors [4,5,6,7,8,9,10,11,12,13,14,15,16], with parabolic cylinder collectors [6,14,17,18] and with linear Fresnel collectors [19]. Also, systems with absorption machines with two or more stages and with various types of solar collectors: with parabolic cylinder collectors [4,20] and with linear Fresnel collectors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Esta herramienta se basa en un modelo matemático integrado que considera las condiciones ambientales, las cargas térmicas del edificio, los datos de pre-dimensionamiento de cada componente del sistema y la interacción simultánea entre ellos, para realizar un análisis preciso, simple y realista. Del caso de estudio, realizado en el mes de julio con 704 m 2 de apertura solar y un tanque de almacenamiento de 35200 L, se obtuvieron 47,5 MWh de energía de refrigeración, con una reducida contribución del sistema auxiliar (5,6 MWh) y una mínima cantidad de horas de desactivación del sistema de captación solar (0,7 %). El coeficiente de rendimiento (COP) diario de la máquina de absorción se mantuvo sobre 0,69.…”
unclassified
“…Simulation and optimization methods for the use of fuel have also been proposed [11][12][13][14][15][16][17][18][19][20]. Environmental issues due to fuel impacts have also been considered and studied [21][22][23][24][25]. Among the types of fuel, the GCV of coal is considered as a primary fuel type for thermal plans.…”
Section: Introductionmentioning
confidence: 99%